2011
DOI: 10.1007/s00268-010-0951-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of a Large Non‐coding RNA Gene XIST in Human Cancer

Abstract: Background X inactive-specific transcript (XIST) RNA is involved in X chromosome silencing in female cells and allows X chromosome equilibration with males. X inactive-specific transcript expression has been found to be dysregulated in a variety of human cancers when compared to normal cells; meanwhile, the inactivated X chromosome has been noted to be conspicuously absent in human cancer specimens, whereas X chromosome duplications are widely noted. The specific pathways whereby changes in X chromosome status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 50 publications
5
102
1
Order By: Relevance
“…Considerable evidence has shown that XIST plays important roles in the differentiation, proliferation and genome maintenance of human cells. Moreover, XIST has been found to be dysregulated in a variety of human cancers, and this dysfunctional expression has been shown to exert a pathological role [16] . Recent studies have suggested that the expression of XIST is associated with glioma stem cells (GSCs) in human glioma [17] .…”
Section: Acta Pharmacologica Sinicamentioning
confidence: 99%
“…Considerable evidence has shown that XIST plays important roles in the differentiation, proliferation and genome maintenance of human cells. Moreover, XIST has been found to be dysregulated in a variety of human cancers, and this dysfunctional expression has been shown to exert a pathological role [16] . Recent studies have suggested that the expression of XIST is associated with glioma stem cells (GSCs) in human glioma [17] .…”
Section: Acta Pharmacologica Sinicamentioning
confidence: 99%
“…LincRNAs not only play critical roles in physical function regulation, such as imprinting (8), but they are also involved in the progress of various diseases including cancer (9)(10)(11). At present, lincRNAs are emerging as either oncogenes or tumor suppressor genes (11)(12)(13)(14)(15). Previous evidence demonstrated the aberrant expression of lincRNAs in digestive system carcinomas (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is considerable evidence that XIST RNA serves other important functions in the differentiation, proliferation and genome maintenance of human cells. Furthermore, loss of XIST RNA expression has been found in female breast, ovarian and cervical cancer cell lines, thus implicating the dysregulation of XIST in oncogenesis (16). Notably, a previous study demonstrated that the deletion of XIST in the hematopoietic cells in mice results in the development of MDS/MPN with 100% penetrance (17).…”
Section: Discussionmentioning
confidence: 97%